Wittgenstein's annotations to Hardy's Course of pure mathematics : an investigation of Wittgenstein's non-extensionalist understanding of the real numbers /: an investigation of Wittgenstein's non-extensionalist understanding of the real numbers. ([2020]) - Floyd, Juliet; Mühlhölzer, Felix
No abstract available